Relationship between learning styles and entrepreneurial competencies among students in a Malaysian university - Chai, Foong Teng (2013)
The purpose of the study was to identify the relationship between learning styles and entrepreneurial competencies among students in a Malaysian university. This is a descriptive study which used a self-administrated questionnaire. The sample was 270 students who enrolled in Entrepreneurship Course as a compulsory course in their respective programme of studies in Universiti Putra Malaysia (UPM). Overall, both Processing strategies (mean=3.16) and Regulation Strategies (mean=3.08) indicated a moderate level. Concrete Processing strategies (mean=3.30;SD=0.68) was found to be the most preferred learning style. Lack of Regulation learning style (mean = 2.98; SD= 0.64) was the least preferred. Literature Programme, Technical programme and Science programme students rated Concrete Processing as their most preferred learning style. The overall students obtained a high level of mean score for management competencies (mean=3.73; standard deviation=.0.58). Marketing competencies (mean=3.67; standard deviation=0.62) and financial competencies (mean=3.46; standard deviation=0.64) are at a moderate level. Overall, the students rated themselves as having a moderate level of entrepreneurial competencies (mean=3.62; standard deviation=0.61). All the subscale of cognitive processing domain: deep processing, stepwise processing and concrete processing were significantly related to management, marketing and financial competencies at a moderate level. The findings showed significant relationships between the different components of learning style and entrepreneurial competencies. The only component of learning styles that had insignificantly negative and negligible relationships with management (r=-.036; p=.372), financial (r= -.110; p=.345), and marketing competencies (r= -.126; p=.606) was Lack of Regulation. It can be concluded that the relationship between learning styles and entrepreneurial competencies among university students are significant. Findings had contributed to improve teaching and learning entrepreneurial competencies at university level.